Du flow binaire au flow polyrythmique, « de la rime scolaire à la rime rappeuse » : une histoire des performances formelles dans le rap en France de Chagrin d’amour à Ärsenik - Idir Mahiou (Itinéraires)
Flow and rhyme, the most common avatars of rhythm in rap, have come a long way in France since Sidney’s imitations of American rap in the early 1980’s. Analysing the rapological practices of Chagrin d’amour, Dee Nasty, IAM and Ärsenik which testify to major changes in many performances recorded in their time, this article offers a compendious description of their evolution, a synthetic chronicle of oratorical and rhyming performances in rap in France, from their genesis from American rap in the 1980’s to the relative stabilization of their formal advances in the early 2000s. During these two essential decades, rap in France gradually forged its formal identity by differentiating itself from the American model and shifting to a French linguistic and cultural background, and went through a “golden age” during which it developed its own complex rhythmic devices that still characterize the discipline today.